Noninvasive assessment of metabolic turnover during inflammation by in vivo deuterium magnetic resonance spectroscopy - Flocke, Vera; Temme, Sebastian; Bouvain, Pascal; Grandoch, Maria; Flögel, Ulrich (Frontiers in Immunology, 2023)
Background: Inflammation and metabolism exhibit a complex interplay, where inflammation influences metabolic pathways and in turn metabolism shapes the quality of immune responses. Here, glucose turnover is of special interest, as proinflammatory immune cells mainly utilize glycolysis to meet their energy needs. Non-invasive approaches to monitor both processes would help elucidate this interwoven relationship to identify new therapeutic targets and diagnostic opportunities. Methods: For induction of defined inflammatory hotspots LPS-doped Matrigel plugs were implanted into the neck of C57BL/6J mice. Subsequently, 1H/19F magnetic resonance imaging (MRI) was used to track the recruitment of 19F-loaded immune cells to the inflammatory focus and deuterium (2H) magnetic resonance spectroscopy (MRS) to monitor the metabolic fate of [6,6-2H2]glucose within the affected tissue. Histology and flow cytometry were used to validate the in vivo in data. Results: After plug implantation and intravenous administration of 19F-containing contrast agent, 1H/19F MRI confirmed infiltration of 19F-labelled immune cells into LPS-doped plugs while no 19F signal was observed in PBS-containing control plugs. Identification of the inflammatory focus was followed by i.p. bolus injection of deuterated glucose and continuous 2H MRS. Inflammation-induced alterations in metabolic fluxes could be tracked with an excellent temporal resolution of two minutes up to 60 minutes after injection and demonstrated a more anaerobic glucose utilization in the initial phase of immune cell recruitment. Conclusions: 1H/2H/19F MRI/MRS was successfully employed for non-invasive monitoring of metabolic alterations in an inflammatory environment paving the way for simultaneous in vivo registration of immunometabolic data in basic research and patients.